Pengaruh Permainan Finger Painting Terhadap Perkembangan Kreativitas Anak di PAUD Pelita Harapan Pasar Latong - Safrida Harahap; Rani Astria Silvera Harahap; Mira Yanti Lubis (Journal of Student Research, 2024)
The purpose of this study is to find out: (1) Development of children's creativity at PAUD Pelita Harapan Pasar Latong, (2) the influence of finger painting games on the development of children's creativity at PAUD Pelita Harapan Pasar Latong. This research uses a quantitative approach with an experimental research type. The research design used a one-group pretest-posttest type pre-experiment . The instruments used consisted of observation and documentation. The data analysis technique used descriptive statistics and conducted a requirement test, namely normality test and homogeneity test. Hypothesis testing using the "t" test. The results showed that: (1) The development of children's creativity at PAUD Pelita Harapan Pasar Latong has developed well, this can be seen from the results of observations of the development of children's creativity during the pretest and during the posttest. The pretest results obtained an average of 13,4 on the posttest obtained an average of 26,9. (2) The results of the "t" test calculation obtainedtcount = 13,76 when compared with the ttable at the 95% confidence level or 5% error rate with free degrees (db) = N - k = 20 - 2 = 18 obtained ttable 2,10. If the price of tcount= 13,76 is compared with ttable = 2,10, it is known that tcount is greater than ttable, (13,76> 2,10). This means that the proposed hypothesis is accepted. That is, there is an influence between finger painting games on the development of children's creativity at PAUD Pelita Harapan Pasar Latong.